Tingkat Kepuasan Pengguna Terhadap Layanan Perpustakaan Majelis Ulama Indonesia (MUI) Sumatera Utara Menggunakan Metode Libqual+TM - Alfi Dalillah Aulia S; Khoirul Jamil; Muslih Fathurrahman (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
User satisfaction is closely related to and depends on the quality of library services. However, even though user satisfaction is an important aspect for library progress, there are still some libraries that do not pay enough attention to the issue of user satisfaction, especially the North Sumatra Indonesian Ulema Council Library. The aim of this research is to determine the level of user satisfaction with the library services of the Indonesian Ulema Council of North Sumatra based on the LibQUAL+TM Method. This research uses a descriptive survey research type with a quantitative approach. The data collection techniques in this research are observation and questionnaires. The results of this research show that user satisfaction with the library services of the Indonesian Ulema Council of North Sumatra is based on the Affect of Service dimension. ) with a score of -0.88, meaning that the service is considered good but does not fully meet the ideal expectations of users. Based on the Information Control dimension, the user assessment is not satisfied with the adequacy gap (AG) with a score of -0.32, meaning the user is not satisfied with the service received and the superiority gap (SG) with a score of -1.79, meaning the service is considered not good and is beyond tolerance zone or completely does not meet the ideal expectations desired by the user. Based on the Library as Place dimensions, it shows an adequacy gap (AG) with a score of 0.55, meaning the user is quite satisfied and a superiority gap (SG) with an assessment score of -0.44, meaning the service is still considered good but does not fully meet the user's ideal expectations.